Pengaruh Media Video Animasi Powtoon berbasis Inquiry Based Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Rahmawati, Richa Dwi; Mujtahid, Iqbal Miftachul (Instructional Development Journal, 2025)
Powtoon animated media comes with various features, tools, and animations that teachers can use as effective learning media in the form of animated videos that motivate students and can improve their critical thinking skills in science learning. Seeing the current development phenomenon, a powtoon animation media was developed with these features, tools, and animation. The purpose of this study was to determine the effect of the use of inquiry-based learning-based powtoon animation video media in improving students' critical thinking skills in science subjects in elementary schools. This type of research is a quasi-experimental research with Nonequivalent Control Group Design. The population of this study were fifth grade students at SDN 016 Bukit Ranah Kampar, totaling 40 students. Data collection techniques using observation and tests. The data obtained and analyzed using statistical analysis techniques, namely the t-test. The results of this study indicate that the use of powtoon animation video media has an effect on the critical thinking skills of fifth grade students at SDN 016 Bukit Ranah. This is evidenced by the t-test with a significance level of 5%, the t table is 2.021. It can be concluded that the tcount is 2.029 > from the ttable, which is 2.021. By obtaining a = 5% for the two-party test. Obtained t table is, 2.201 it can be concluded that tcount is obtained 2.209> from ttable which is 2.021. Thus Hₒ is rejected and Hₐ is accepted. This shows that the critical thinking skills of the two groups are significantly different. The difference in the posttest average scores on the results of students' critical thinking skills in the experimental and control classes, the experimental class that was treated using the Powtoon animation video media had an average score of 76.5, while the control class obtained an average score of 67.5, so it can be concluded that there is a significant effect of the use of powtoon animation video media on students' critical thinking skills. For this reason, it is hoped that teachers can maximize the use of effective learning media in the form of powtoon animated video media.